Preclinical imaging of kallikrein-related peptidase 2 (hK2) in prostate cancer with a (111)In-radiolabelled monoclonal antibody, 11B6 - Timmermand, Oskar Vilhelmsson (EJNMMI Res, 2014)
BACKGROUND: Prostate cancer is a leading cause of death in the male population of the western world. Human kallikrein-related peptidase 2 (hK2) is abundantly expressed in malignant prostatic tissue, and its gene, KLK2, is regulated by the androgen receptor. 11B6 is a murine IgG(1) monoclonal antibody directed against free human hK2. In this study, we performed a preclinical evaluation of (111)In-labelled 11B6 in mouse xenografts to investigate its potential in the clinical staging and assessment of metastatic prostate cancer. METHODS: 11B6 was radiolabelled with (111)In through CHX-A″-DTPA chelation. In vivo biodistribution and uptake of (111)In-DTPA-11B6 were measured until 168 h post-injection in NMRI nude mice bearing subcutaneous LNCaP xenografts. The binding specificity to hK2 was evaluated by both in vivo competitive binding assays with excess non-labelled 11B6 and hK2-negative DU145 xenografts. SPECT/CT imaging of subcutaneous and intra-tibial LNCaP xenografts was used to visualize the tumours. RESULTS: Tumour uptake of (111)In-DTPA-11B6 in LNCaP xenografts was 19% ± 0.78%IA/g at 48 h, giving a tumour-to-blood ratio of 1.6, which increases to 2.4 at 1 week post-injection. Accumulation was low in other organs except for the salivary glands, which is probably the result of cross-reactivity with mouse kallikreins. Significantly lower tumour accumulation was observed in competitive assays and DU145 xenografts. SPECT/CT imaging could clearly visualize the subcutaneous and intra-tibial LNCaP xenografts. CONCLUSIONS: Our study demonstrates the potential of (111)In-DTPA-11B6 for the detection of metastatic prostate cancer and monitoring anti-androgen therapy, as it exhibits an increased uptake and accumulation in viable tumour when compared to normal tissue. A humanised version of the 11B6 monoclonal antibody is currently under evaluation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13550-014-0051-5) contains supplementary material, which is available to authorized users.